Molecular Mechanism of Puerarin Against Diabetes and its Complications - Bai, Yi-ling; Han, Ling-ling; Qian, Jun-hui; Wang, Hao-zhong (Frontiers in Pharmacology, 2022)
Puerarin is a predominant component of Radix Puerarin. Despite its anti-tumor and anti-virus effects and efficacy in improving cardiovascular or cerebrovascular diseases and preventing osteoporosis, it has been shown to protect against diabetes and its complications. This review summarizes the current knowledge on Puerarin in diabetes and related complications, aiming to provide an overview of antidiabetic mechanisms of Puerarin and new targets for treatment.